INTUITIONISTIC FUZZY SETS IN MEDICAL DIAGNOSIS - EDWARD SAMUEL, A.; NARMADHAGNANAM, R. (International Journal of Mathematical Archive, 2018)
In this paper, tangent inverse distance and sine similarity measure between intuitionistic fuzzy sets are proposed and some of its properties are discussed herein. The concept of the above methods are the essential tool for dealing with uncertainties and shortcomings that affect the existing methods. Implementation of medical diagnosis is presented to find out the disease impacting the patient.